Manajemen Pendidikan Anak Usia Dini (Urgensi Kearsipan dalam Menghadapi Akreditasi) - M Sahrawi Saimima; Sawal Mahaly (IAIN AMBON, 2022)
Management is the activity of planning, organizing and controlling the program of activities to be carried out In the process of its application, management is needed for Early Childhood Education Institutions. In today's technological era, archival systems do not only require expertise to document archives manually. Instead, it is online through the available applications. This research uses the Action research method, which is research that talks about, for and by the community by utilizing interaction, participation and collaboration with the target group. The results of the study showed that PAUD Wastalele Indah and KB Sepakat Al Hidayah 5, can receive input well and take part in document filing training through google drive which has been carried out with the main objective of making it easier for them to face accreditation in the future. Keywords; PAUD Management, Archives, Accreditation